Monoclonal and polyclonal immunoglobulin G deposits on tubular basement membranes of native and pretransplant kidneys: A retrospective study. Issue 6 (30th March 2021) - Sawada, Anri; Okumi, Masayoshi; Horita, Shigeru; Tamura, Tomomi; Taneda, Sekiko; Ishida, Hideki; Hattori, Motoshi; Tanabe, Kazunari; Nitta, Kosaku; Honda, Kazuho; Koike, Junki; Nagashima, Yoji; et al.
Abstract : Monoclonal tubular basement membrane immune deposits (TBMID) are associated with progression of interstitial injury in renal allograft. However, the significance of monoclonal and polyclonal TBMID in the native kidney remains unclear. We retrospectively analyzed 1894 native kidney biopsies and 1724 zero‐hour biopsies performed between 2008 and 2018 in our institution. The rate of immunoglobulin G (IgG) TBMID was found to be 8.4% among native kidney biopsies and 0.4% among zero‐hour biopsies. Polyclonal TBMID is common in IgG4‐related tubulointerstitial nephritis (37.5%), diabetic nephropathy (31.3%) and lupus nephritis (25.5%). Monoclonal IgG TBMID was identified in seven cases, including three zero‐hour biopsies. The combination of IgG1κ was observed in two cases, IgG1λ in three, and IgG2κ in two. Electron microscopy revealed powdery electron‐dense deposits in all cases. Monoclonal gammopathy of undetermined significance was diagnosed in one case. Although one patient with focal segmental glomerulosclerosis developed renal failure, all others exhibited stable renal function. Monoclonal IgG TBMID in the native kidney is not associated with renal prognosis. However, this may be an interesting immunopathological finding that would help clarify the pathogenesis of TBM immune deposits. Further study for both monoclonal and polyclonal TBMID is required in the future.